2013
DOI: 10.1007/s10096-013-1969-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromoblastomycosis as an endemic disease in temperate Europe: first confirmed case and review of the literature

Abstract: This study reports a case of a 56-year-old white male, retired coal-miner, diagnosed with chromoblastomycosis lasting 20 years. The infection site was the burnt skin of the back. For many years the patient had not undertaken any treatment believing that the lesion had been a burn scar. A gradual increase in lesion size prompted the patient to start therapy. The diagnosis was made by histopathological examination and mycological culture. Identification of the causative agent at the species level was achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 22 publications
0
41
0
1
Order By: Relevance
“…A recent review of CBM in Europe revealed a total of 31 probable cases (149). The authors of that study suggested that the disease was considered to be autochthonous in some cases.…”
Section: Chromoblastomycosis In Europementioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of CBM in Europe revealed a total of 31 probable cases (149). The authors of that study suggested that the disease was considered to be autochthonous in some cases.…”
Section: Chromoblastomycosis In Europementioning
confidence: 99%
“…The authors of that study suggested that the disease was considered to be autochthonous in some cases. One of these cases was an infection acquired in a mine from locally harvested mine wood and caused by F. monophora (149). As CBM is uncommon in Europe, cases may have been misdiagnosed as cutaneous tuberculosis, squamous cell carcinoma, psoriasis, PHM, and sporotrichosis or other infectious and noninfectious conditions that may mimic CBM.…”
Section: Chromoblastomycosis In Europementioning
confidence: 99%
“…It should be considered in travelers from endemic regions showing corresponding clinical signs [5]. Albeit rarely, autochthonous infections have also been described in Central Europe [6].…”
Section: Discussionmentioning
confidence: 99%
“…Besonders bei Reisenden aus Endemiegebieten mit entsprechender Klinik gilt es daran zu denken [5]. Autochthone Infektionen in Zentraleuropa sind selten, werden aber beschrieben [6].…”
Section: Diskussionunclassified